PERBANDINGAN PERFORMA PERTUMBUHAN PADA SAPI PERANAKAN ONGOLE DI DESA PURWODADI DALAM DAN DESA WAWASAN, KECAMATAN TANJUNGSARI, KABUPATEN LAMPUNG SELATAN - Ega Kurniawan; Ali Husni; Sulastri Sulastri; Kusuma Adhianto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This research aimed to compare the growth performance of Ongole Grade (PO) cattle in Purwodadi Dalam and Wawasan villages. This research was conducted from December 2019 to January 2020 at the People's Animal Husbandry Center, Wawasan Village and Purwodadi Dalam Village, Tanjungsari District, South Lampung Regency, Lampung Province. This study used a survey method (purposive sampling), using primary and secondary data. The observed variables were birth weight, weaning weight and yearling weight. The results showed that the average weight gain of PO cattle in the village of Wawasan was 84.33 ± 19.18 kg / head, which was higher than that of Purwodadi Dalam, namely 80.17 ± 19.49 kg / head. The body weight gain after weaning of PO cattle in Wawasan Village was 39.15 ± 21.34 kg, higher than that in Purwodadi Dalam Village, namely 37.75 ± 21.10 kg / head. The body weight gain from birth to one year of PO cattle in Wawasan Village was 123.49 ± 26.26 kg / head, which was also higher than that in Purwodadi Dalam Village, namely 117.93 ± 30.50 kg / head. The results also showed that the corrected weaning weight of PO cattle in Wawasan Village (122.40 ± 23.20 kg / head) was higher than that in Purwodadi Dalam Village (121.24 ± 22.86 kg / head), and the average body weight of one year old of PO cattle in Wawasan Village was 147.95 ± 26.58 kg / head higher than that in Purwodadi Dalam Village with an average weight of 141.98 ± 31.37 kg / head. The results of the current study concluded that the growth performance of PO cattle in Wawasan Village was better than those in Purwodadi Dalam Village. Keywords: Growth performance, Ongole Grade (PO) cattle, Weaning weight, Yearling weight